Clinical implications of genetic testing for BRCA1 and BRCA2 mutations in Austria. (16th July 2013) - Singer, CF; Muhr, D; Rappaport, C; Tea, M‐K; Gschwantler‐Kaulich, D; Fink‐Retter, A; Pfeiler, G; Berger, A; Sun, P; Narod, SA
<x xml:space="preserve">Abstract</x> The objective of this study was to describe the experience of genetic testing in Austrian women with a BRCA1 or BRCA2 mutation in terms of preventive measures taken and incident cancers diagnosed. We collected clinical information on 246 Austrian women with a BRCA1 or BRCA2 mutation tested between 1995 and 2012 and followed 182 of them for an average of 6.5 years. Of the 90 women who were cancer‐free at baseline, 21.4% underwent preventive bilateral mastectomy, 46.1% had preventive bilateral salpingo‐oophorectomy, and 1 took tamoxifen; 58.8% of the at‐risk women underwent at least one screening breast magnetic resonance imaging (MRI). Of the 85 women with breast cancer, 69.4% had a unilateral mastectomy or lumpectomy and 30.6% had a contralateral mastectomy. In the follow‐up period, 14 new invasive breast cancers (6 first primary and 8 contralateral), 1 ductal carcinoma in situ case, 2 incident ovarian cancer cases, and 1 peritoneal cancer were diagnosed. In Austria, the majority of healthy women with a BRCA1 or BRCA2 mutation opt for preventive oophorectomy and MRI screening to manage their breast cancer risk; few have preventive mastectomy or take tamoxifen.